Hafnium aluminum oxide coatings deposited by atomic layer deposition
A hafnium aluminum oxide coating deposited via ALD addresses the corrosion issues in semiconductor processing chambers, enhancing plasma resistance and reducing contamination, while maintaining structural integrity and cost-effectiveness.
Patent Information
- Application Number
- JP2022523433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2020-10-22
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2040-10-22
AI Technical Summary
Plasma etch and cleaning processes in the semiconductor industry cause corrosion of processing chamber components, leading to particle contamination and device defects, with existing ceramics exhibiting varying degrees of plasma resistance, cost, bending strength, and thermal shock resistance, and failing to coat high aspect ratio features effectively.
A corrosion-resistant hafnium aluminum oxide coating is deposited using atomic layer deposition (ALD) with compositions ranging from 1 mol% to 40 mol% hafnium and aluminum, and the balance oxygen, providing a conformal, amorphous, and uniform coating suitable for chamber components with high aspect ratios.
The hafnium aluminum oxide coating exhibits superior corrosion resistance in plasma environments, reducing metal and particle contamination, maintaining integrity under high temperatures, and extending the lifespan of chamber components.
Smart Images

Figure 0007604476000006 
Figure 0007604476000007 
Figure 0007604476000008
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present disclosure relate to corrosion-resistant hafnium aluminum oxide coatings, coated articles, and methods of forming such coatings using atomic layer deposition. [Background technology]
[0002] In the semiconductor industry, devices are manufactured by a number of manufacturing processes that produce structures of ever-decreasing size. Some manufacturing processes, such as plasma etching and plasma cleaning processes, expose a substrate to a high velocity flow of plasma to etch or clean the substrate. Plasma is highly corrosive and can corrode the processing chamber and other surfaces and components exposed to the plasma. Such corrosion can produce particles that frequently contaminate the substrate being processed and cause device defects. Halogen-containing plasmas, which can contain halogen ions and radicals, can be particularly harsh, resulting in particles generated from the interaction of the plasma with materials in the processing chamber. Plasma can also cause drift in the wafer process due to changes in the surface chemistry of the components induced by radical recombination.
[0003] As device geometries shrink, susceptibility to defects increases and particulate contamination specifications (i.e., on-wafer performance) become more stringent. To minimize particulate contamination introduced by plasma etching and / or plasma cleaning processes, plasma-resistant chamber materials have been developed. Examples of such plasma-resistant materials include ceramics composed of Al2O3, AlN, SiC, Y2O3, quartz, and ZrO2. Different ceramics offer different material properties such as plasma resistance, stiffness, bending strength, and thermal shock resistance. Different ceramics also have different material costs. Thus, some ceramics have better plasma resistance, others have lower costs, and still others have better bending strength and / or thermal shock resistance.
[0004] Plasma spray coatings made of Al2O3, AlN, SiC, Y2O3, quartz, and ZrO2 can reduce particle generation from chamber parts, but such plasma spray coatings cannot penetrate and coat high aspect ratio features such as gas lines and holes in a showerhead. Some deposition techniques can coat high aspect ratio features, but the resulting coatings can erode in certain plasma environments, e.g., halogen-containing plasmas, forming particles, or have problems with mechanical separation of material layers due to poor interdiffusion in the coating. Summary of the Invention
[0005] According to embodiments described herein, a coated article includes a body and a corrosion resistant coating on a surface of the body. The corrosion resistant coating can include hafnium aluminum oxide including about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and balance oxygen, where the hafnium aluminum oxide includes about 20 mol % to about 98 mol % oxygen.
[0006] Further described in embodiments herein is a method comprising depositing a corrosion resistant coating on a surface of an article using atomic layer deposition. The corrosion resistant coating may comprise about 1 mol% to about 40 mol% hafnium, about 1 mol% to about 40 mol% aluminum, and the remaining mol% oxygen. The article may comprise a part of a processing chamber selected from the group consisting of a chamber wall, a showerhead, a nozzle, a plasma generating unit, a radio frequency electrode, an electrode housing, a diffuser, and a gas line.
[0007] Further described herein is a method that includes depositing a hafnium aluminum oxide coating on a surface of an article using atomic layer deposition. Depositing the hafnium aluminum oxide coating may include contacting the surface with a hafnium-containing precursor or with an aluminum-containing precursor for a first duration to form a first adsorbed layer. Depositing the hafnium aluminum oxide coating may further include contacting the first adsorbed layer with an oxygen-containing reactant to form a first layer comprising hafnium oxide or aluminum oxide. Depositing the hafnium aluminum oxide coating may further include contacting the first layer with an aluminum-containing precursor or with a hafnium-containing precursor for a second duration to form a second adsorbed layer. Depositing the hafnium aluminum oxide coating may further include contacting the second adsorbed layer with an oxygen-containing reactant to form a second layer comprising aluminum oxide or hafnium oxide. In one embodiment, when the first layer comprises hafnium oxide, the second layer comprises aluminum oxide, and when the first layer comprises aluminum oxide, the second layer comprises hafnium oxide. The method may also include forming a hafnium aluminum oxide coating from the first layer and the second layer. The corrosion resistant coating may include hafnium aluminum oxide including about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and balance oxygen, where the hafnium aluminum oxide includes about 20 mol % to about 98 mol % oxygen. [Brief description of the drawings]
[0008] The present disclosure is illustrated by way of example, and not by way of limitation, in the accompanying drawings, in which like elements are designated with like reference numerals, and in which: It should be noted that various references to "an" or "one" embodiment in this disclosure are not necessarily to the same embodiment, and such references mean at least one.
[0009] [Figure 1] 1 is a cross-sectional view of a processing chamber. [Figure 2A] 1 illustrates one embodiment of a co-deposition process according to the atomic layer deposition technique described herein. [Figure 2B] 1 illustrates another embodiment of a co-deposition process according to the atomic layer deposition technique described herein. [Figure 2C] 1 illustrates one embodiment of a continuous deposition process according to the atomic layer deposition techniques described herein. [Diagram 3] Figure 3A is a transmission electron microscope image of successively deposited Hf2Al2O7 coatings, and Figure 3B is a transmission electron microscope image of successively deposited HfAl2O5 coatings. [Figure 4]FIG. 4A1 is a digital camera image of an uncoated stainless steel specimen after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. FIG. 4A2 is an optical microscope image of a first pit cross-section of an uncoated stainless steel specimen after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. FIG. 4A3 is an optical microscope image of a second pit cross-section of an uncoated stainless steel specimen after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. FIG. 4B1 is a digital camera image of a stainless steel specimen coated with a 100 μm HfAl2O5 coating after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. FIG. 4B2 is an optical microscope image of a pit cross-section of a stainless steel specimen coated with a 100 μm HfAl2O5 coating after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. FIG. 4B3 is an optical microscope image of a pit-free cross-section of a stainless steel specimen coated with an approximately 100 μm HfAl2O5 coating after undergoing a 6% FeCl3 immersion test at approximately 50° C. for approximately 12 hours. FIG. 4C1 is a digital camera image of a stainless steel specimen coated with an approximately 100 μm Hf2Al2O7 coating after undergoing a 6% FeCl3 immersion test at approximately 50° C. for approximately 12 hours. FIG. 4C2 is an optical microscope image of a pit-free cross-section of a stainless steel specimen coated with an approximately 100 μm Hf2Al2O7 coating after undergoing a 6% FeCl3 immersion test at approximately 50° C. for approximately 12 hours. FIG. 4C3 is an optical microscope image of a pit-free cross-section of a stainless steel specimen coated with an approximately 100 μm Hf2Al2O7 coating after undergoing a 6% FeCl3 immersion test at approximately 50° C. for approximately 12 hours. FIG. 4D1 is a digital camera image of a stainless steel coupon coated with an approximately 100 μm Al2O3 coating after being subjected to a 6% FeCl3 immersion test for approximately 12 hours at approximately 50° C. FIG. 4D2 is an optical microscope image of a first pit cross section of a stainless steel coupon coated with an approximately 100 μm Al2O3 coating after being subjected to a 6% FeCl3 immersion test for approximately 12 hours at approximately 50° C.FIG. 4D3 is an optical microscope image of a second pitted cross section of the stainless steel specimen coated with about a 100 μm Al2O3 coating after being subjected to a 6% FeCl3 immersion test at about 50° C. for about 12 hours. [Diagram 5] FIG. 2 illustrates an exploded view of a gas line having a large aspect ratio coated with a corrosion resistant coating according to one embodiment. [Figure 6] Figure 6A is a transmission electron microscope image of a Hf2Al2O7 coating on an aluminum specimen before a Cl2 immersion test at a scale of 20 nm, and Figure 6B is a transmission electron microscope image of the Hf2Al2O7 coating of Figure 6A after a Cl2 immersion test at a scale of 20 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Embodiments described herein relate to hafnium aluminum oxide corrosion resistant coatings for improving the corrosion / erosion resistance of chamber components in plasma or corrosive non-plasma environments. The embodiments also relate to coated articles (e.g., chamber components) and methods of forming such corrosion resistant coatings using atomic layer deposition (ALD).
[0011] In the semiconductor industry, some manufacturing processes, such as plasma etching and plasma cleaning processes, expose substrates to high velocity plasma flows to etch or clean the substrate. Plasma is highly corrosive and can corrode the processing chamber and other surfaces and components exposed to the plasma. Such corrosion can produce particles that frequently contaminate the substrate being processed and cause device defects. Halogen-containing plasmas, which can include halogen ions and radicals, can be particularly harsh, resulting in particles generated from the interaction of the plasma with materials in the processing chamber. Plasma can also cause drift in wafer processes due to changes in surface chemistry of components induced by radical recombination.
[0012] Chamber parts (e.g., stainless steel and aluminum parts) coated with hafnium aluminum oxide coatings deposited by ALD have been found to have greater corrosion resistance in Cl-based solutions compared to uncoated parts and alumina-coated parts. x Al y O z By using coated chamber parts, metal / particle contamination on the wafer (i.e., substrate) can be reduced to a greater extent than can currently be achieved with alumina coated parts. Superior corrosion resistance can be achieved with thin hafnium aluminum oxide, which allows for a more cost-effective corrosion resistant coating. Furthermore, the hafnium aluminum oxide coating can withstand relatively high temperatures without cracking or failure, as opposed to traditional coatings.
[0013] In some embodiments, the corrosion resistant coating can include about 1 mol% to about 40 mol% hafnium, about 1 mol% to about 40 mol% aluminum, and the balance oxygen, and the amount of oxygen in the coating can be about 20 mol% to about 98 mol%. In other embodiments, the corrosion resistant coating can include about 10 mol% to about 20 mol% hafnium, about 15 mol% to about 30 mol% aluminum, and the balance oxygen. In some embodiments, the corrosion resistant coating can be a homogenous mixture of hafnium and aluminum having an aluminum to hafnium molar ratio ranging from about 0.8 to about 2.5. In one embodiment, the corrosion resistant coating can include at least one of HfAl2O5 or Hf2Al2O7.
[0014] The article that can be coated with the corrosion-resistant coating described herein can include a processing chamber component selected from the group consisting of a chamber wall, a showerhead, a nozzle, a plasma generating unit, a radio frequency electrode, an electrode housing, a diffuser, and a gas line. In some embodiments, the article that can be coated with the corrosion-resistant coating described herein can include a portion having a depth-to-width aspect ratio ranging from about 10:1 to about 200:1, and this portion of the article having the aspect ratio can be coated with the corrosion-resistant coating. For example, the surface of a gas line can be coated with a corrosion-resistant coating according to one embodiment.
[0015] The corrosion resistant coating can be conformal, amorphous, have low porosity (e.g., about 0%), and / or have a uniform thickness (e.g., less than about + / - 5% thickness variation). In some embodiments, the corrosion resistant coating can have a thickness ranging from about 0.5 nm to about 1 μm, or another thickness therein.
[0016] In some embodiments, the corrosion resistant coating exhibits its corrosion resistance by an HCl bubble test, and / or by an FeCl3 soak test, and / or by an HCl soak test, and / or by a dichlorosilane (DSC) exposure test, and / or by a Cl2 soak test, which are described in more detail below.
[0017] For example, in one embodiment, a corrosion resistant coating having a thickness of about 300 nm may exhibit a longer failure life in an HCl bubble test conducted in a 5% HCl solution or a 15% HCl solution compared to a thicker alumina coating or compared to a thicker yttrium silicon oxide coating. For example, a corrosion resistant coating at a thickness of about 300 nm may exhibit at least one of a) at least about 13 hours to failure when tested by an HCl bubble test conducted in a 5% HCl solution, or b) at least about 10 hours to failure when tested by an HCl bubble test conducted in a 15% HCl solution.
[0018] In another embodiment, a corrosion resistant coating of hafnium aluminum oxide having a thickness of about 100 nm exhibits less pitting corrosion than an aluminum oxide coating of the same thickness in a 6% FeCl3 immersion test conducted for about 12 hours at about 50° C. In yet another embodiment, the hafnium aluminum oxide coating enhances the corrosion resistance of stainless steel as measured in an HCl immersion test, compared to an alumina coating of the same thickness.
[0019] In one embodiment, the hafnium aluminum oxide corrosion resistant coating does not produce metal contamination of the wafer after about 900 wafer processing cycles (about 45 minutes) at temperatures ranging from about 150° C. to about 180° C. in a processing environment in which the coating is exposed to dichlorosilane.
[0020] In one embodiment, a corrosion resistant coating of hafnium aluminum oxide does not corrode (e.g., as evidenced by a change in thickness) when the coating is immersed in Cl2 at 380° C. for about 25 hours in a vacuum chamber.
[0021] In some embodiments, the hafnium aluminum oxide corrosion resistant coating, at a thickness of about 300 nm, requires a force of at least about 52 mN, at least about 75 mN, at least about 80 mN, or at least about 100 mN to expose the surface of the body using a 10 micron diamond stylus in a scratch adhesion test.
[0022] As described in more detail below, the corrosion resistant coating may be co-deposited, co-doped, or sequentially deposited onto the article using non-line-of-sight techniques such as atomic layer deposition (ALD).
[0023] The coatings described herein can also be resistant to erosion upon exposure to plasma chemistries used in semiconductor processing and chamber cleaning, such as halogen-containing plasmas having halogen ions and halogen radicals. Thus, the coatings provide good particle and process stability performance during such processing and cleaning procedures. As used herein, the term "erosion-resistant coating" or "plasma-resistant coating" refers to a coating that has a particularly low erosion rate when exposed to certain plasmas, chemistries and radicals (e.g., fluorine-based plasmas, chemicals and / or radicals, bromine-based plasmas, chemicals and / or radicals, chlorine-based plasmas, chemicals and / or radicals, etc.).
[0024] The erosion and corrosion resistant coatings described herein may also be resistant to halogen non-plasma corrosive environments, such as halogens (e.g., chlorine, fluorine, bromine, etc.) and any halogen-containing compounds (e.g., chlorine-containing compounds, fluorine-containing compounds, bromine-containing compounds, etc.).
[0025] The resistance of a coating to plasma can be measured by the "etch rate" (ER), which may have units of angstroms per minute (Å / min), throughout the duration of operation of the coated part and exposure to the plasma. Plasma resistance can also be measured by erosion rate, which has units of nanometers per radio frequency hour (nm / RFHr), where 1 RFHr represents 1 hour of treatment at the plasma treatment conditions. Measurements can be taken after different treatment times. For example, measurements can be taken before treatment, after 50 treatment hours, 150 treatment hours, 200 treatment hours, etc. Erosion rates below about 100 nm / RFHr in halogen plasmas are typical for erosion-resistant coatings. Variations in the composition of the coating deposited on the chamber parts can result in multiple different plasma resistance or erosion rate values. In addition, a erosion-resistant coating with one composition exposed to various plasmas could have multiple different plasma resistance or erosion rate values. For example, a particular coating may have a first plasma resistance or erosion rate associated with a first type of plasma, or a second plasma resistance or erosion rate associated with a second type of plasma.
[0026] 1 is a cross-sectional view of a semiconductor processing chamber 100 having one or more chamber parts coated with a corrosion-resistant coating according to embodiments described herein. The substrate of at least some of the components of the chamber is Al (e.g., Al x O y , AlN, Al 6061, or Al 6063), Si (e.g., Si x O y, SiO2, or SiC), copper (Cu), magnesium (Mg), titanium (Ti), and stainless steel (SST). The processing chamber 100 can be used for processes in which a corrosive plasma environment (e.g., halogen plasma, such as chlorine-containing plasma, fluorine-containing plasma, bromine-containing plasma, etc.) is provided. For example, the processing chamber 100 can be a chamber for a plasma etcher or plasma etch reactor, a plasma cleaner, a plasma CVD or ALD reactor, etc. Examples of chamber parts that include a corrosion-resistant coating include chamber parts having features with complex shapes and high aspect ratios. Some exemplary chamber parts include a substrate support assembly, an electrostatic chuck, a ring (e.g., a process kit ring or a single ring), a chamber wall, a base, a gas distribution plate, a showerhead, a gas line, a nozzle, a lid, a liner, a liner kit, a shield, a plasma screen, a plasma generating unit, a radio frequency electrode, an electrode housing, a diffuser, a flow equalizer, a cooling base, a chamber viewport, a chamber lid, etc.
[0027] In some embodiments, a chamber part coated with the corrosion-resistant coating described herein can include a portion having a high depth-to-width aspect ratio in the range of about 3:1 to about 300:1 (e.g., about 5:1 to about 250:1, about 10:1 to about 200:1, about 20:1, about 50:1, about 100:1, about 150:1, etc.), where the portion of the article having the aspect ratio can be coated with the corrosion-resistant coating. For example, according to one embodiment, the inner surface of a gas line or the inner surface of a gas conduit of a showerhead can be coated with a corrosion-resistant coating.
[0028] 5 is an exploded view of a gas line having a large aspect ratio coated with a corrosion resistant coating, according to one embodiment. The gas line 510 can have a depth D and a width W. The gas line 510 can have a large aspect ratio, defined as D:W, where the aspect ratio can range from about 3:1 to about 300:1 (e.g., about 5:1 to about 250:1, about 10:1 to about 200:1, about 50:1 to about 100:1, about 20:1, about 50:1, about 100:1, about 150:1, etc.). In some embodiments, the aspect ratio can be less than 3:1 or greater than 300:1.
[0029] Gas line 510 can have an interior surface 555. Interior surface 555 can be made of aluminum, stainless steel, or any of the other materials of construction described herein. Interior surface 555 can be coated with a corrosion resistant coating using ALD, as described with reference to Figures 2A, 2B, or 2C. The ALD process can grow conformal coating layers 560 and 565 of uniform thickness across the entire interior surface of gas line 510 despite its large aspect ratio, while also ensuring that the final corrosion resistant coating is thin enough so as not to clog the gas line.
[0030] Referring again to FIG. 1 , in one embodiment, the processing chamber 100 includes a chamber body 102 and a showerhead 130 that surround an interior space 106. The showerhead 130 may include a showerhead base and a showerhead gas distribution plate. Alternatively, the showerhead 130 may be replaced by a lid and a nozzle in some embodiments, or by a plurality of pie-shaped showerhead sections and a plasma generating unit in other embodiments. The chamber body 102 may be fabricated from aluminum, stainless steel, or other suitable materials. The chamber body 102 typically includes a sidewall 108 and a bottom 110. An outer liner 116 may be disposed adjacent to the sidewall 108 to protect the chamber body 102. Any of the showerhead 130 (or the lid and / or nozzle), the sidewall 108, and / or the bottom 110 may include any of the corrosion-resistant coatings described herein.
[0031] An exhaust port 126 is defined in the chamber body 102 and may connect the interior volume 106 to a pumping system 128. The pumping system 128 may include one or more pumps and a throttle valve utilized to evacuate the interior volume 106 of the processing chamber 100 and to regulate the pressure in the interior volume 106.
[0032] The showerhead 130 may be supported on a sidewall 108 of the chamber body 102. The showerhead 130 (or lid) may be open to allow access to the interior volume 106 of the processing chamber 100 and may provide a seal for the processing chamber 100 while closed. A gas panel 158 may be coupled to the processing chamber 100 to provide process gases and / or cleaning gases to the interior volume 106 through the showerhead 130 or the lid and nozzles. The showerhead 130 may be used for processing chambers used for dielectric etching (etching of dielectric materials). The showerhead 130 includes a gas distribution plate (GDP) with a number of gas delivery holes 132 extending therethrough. The showerhead 130 may include a GDP bonded to an aluminum base or an anodized aluminum base. The GDP may be made of Si or SiC, or may be made of YO, AlO, YAlO, or other suitable materials. 12 It can be a ceramic such as (YAG) or the like.
[0033] A processing chamber used for conductor etching (etching conductive materials) may use a lid rather than a showerhead. The lid may include a central nozzle that fits into a central hole in the lid. The lid may be a ceramic such as Al2O3, Y2O3, YAG, or a ceramic compound including a solid solution of Y4Al2O9 and Y2O3-ZrO2. The nozzle may also be a ceramic such as Y2O3, YAG, or a ceramic compound including a solid solution of Y4Al2O9 and Y2O3-ZrO2.
[0034] Examples of process gases that can be used to process a substrate in the process chamber 100 include halogen-containing gases, such as C2F6, SF6, SiCl4, HBr, NF3, CF4, CHF3, CH2F3, F, NF3, Cl2, CCl4, BCl3, and SiF4, among others, as well as other gases such as O2, or N2O. Examples of carrier and purge gases include N2, He, Ar, and other gases that are inert (e.g., non-reactive) with respect to the process gas.
[0035] The substrate support assembly 148 is disposed in the interior volume 106 of the processing chamber 100 below the showerhead 130 or lid. The substrate support assembly 148 includes a support 136 that supports a substrate 144 during processing. The support 136 is attached to the end of a shaft (not shown) that is coupled to the chamber body 102 via a flange 164. The substrate support assembly 148 may include, for example, a heater, an electrostatic chuck, a susceptor, a vacuum chuck, or other substrate support assembly components.
[0036] Any of the aforementioned components of the processing chamber 100 may include a corrosion resistant coating, which is described in further detail below. The corrosion resistant coating may include about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and the balance oxygen, where the amount of oxygen in the coating may be about 20 mol % to about 98 mol %.
[0037] Figure 2A illustrates one embodiment of a co-deposition process 200 by ALD techniques to grow or deposit a hafnium aluminum oxide coating on an article (e.g., on any of the chamber components described with reference to Figure 1). Figure 2B illustrates another embodiment of a co-deposition process 204 by ALD techniques described herein to grow or deposit a hafnium aluminum oxide coating on an article. Figure 2C illustrates another embodiment of a sequential deposition process 208 by ALD techniques to grow or deposit a hafnium aluminum oxide coating described herein.
[0038] With respect to the ALD codeposition processes 200 and 204, the adsorption of at least two precursors onto a surface, or the reaction of a reactant with the adsorbed precursors, can be referred to as a "half-reaction."
[0039] During a first half-reaction in process 200, a first precursor 210 (or a first mixture of precursors) can be pulsed onto a surface of article 205 for a period of time sufficient to allow the precursor to partially (or completely) contact and adsorb onto the surface of the article (including surfaces of pores and features within the article). In some embodiments, the first precursor can be pulsed into the ALD chamber for a first duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. The first precursor 210 (or first mixture of precursors) can be a hafnium-containing precursor and / or an aluminum-containing precursor.
[0040] Adsorption is self-limiting as the precursor adsorbs onto a number of available sites on the surface, forming a partial adsorption layer of the first metal 215 (e.g., hafnium and / or aluminum) on the surface. Any sites already adsorbed with the first metal of a precursor will be unavailable for further adsorption with a subsequent precursor. Alternatively, some sites adsorbed with the first metal of a first precursor may be replaced with the second metal of a second precursor adsorbing on the sites.
[0041] To complete the first half-reaction, the second precursor 220 (or optionally a second mixture of precursors) can be pulsed onto the surface of the article 205 for a second duration sufficient to allow the second metal of the second precursor to adsorb (partially or completely) onto available sites on the surface (and possibly replace a portion of the first metal of the first precursor) to form a codeposited adlayer (e.g., layer 225 in FIG. 2A ) on the surface. In some embodiments, the second precursor can be pulsed into the ALD chamber for a second duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. The second precursor (or second mixture of precursors) can be a hafnium-containing precursor and / or an aluminum-containing precursor. For example, when the first precursor includes a hafnium-containing precursor, the second precursor can include an aluminum-containing precursor, and when the first precursor includes an aluminum-containing precursor, the second precursor can include a hafnium-containing precursor.
[0042] Excess precursor can then be flushed or purged (i.e., with an inert gas) from the ALD chamber before reactant 230 is introduced into the ALD chamber. In some embodiments, reactant can be introduced into the ALD chamber for a duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. In the case of an oxide coating, the reactant can be an oxygen-containing reactant. The oxygen-containing reactant 230 reacts with the co-adsorbed layer (225 in FIG. 2A) to form a coating layer 235 (e.g., Hf x Al y O z After formation of the oxygen-containing reactant, any excess oxygen-containing reactant can be flushed from the ALD chamber. Alternatively, or in addition, the ALD chamber may be purged during the first half-reaction between deposition of the first and second precursors.
[0043] As shown in FIG. 2B, the article 205 can be inserted into an ALD chamber. In this embodiment, the codeposition process involves the simultaneous co-addition of at least two precursors onto the surface of the article. The article 205 can be introduced into the mixture of precursors 210, 220 (e.g., one or more hafnium-containing precursors and one or more aluminum-containing precursors) for a certain duration until the surface of the article or the body of the article fully contacts and adsorbs with the mixture of precursors 210, 220 to form a co-adsorbed layer 227. In some embodiments, the mixture of the first and second precursors can be pulsed into the ALD chamber for a first duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. A mixture of precursors 210, 220 (also referred to herein as precursors A and B) may be co-injected (A) into the chamber in any ratio, e.g., A90+B10, A70+B30, A50+B50, A30+B70, A10+A90, etc. x B y ) and can be adsorbed onto the surface of the article. In these examples, x and y are expressed as the atomic ratio (mol%) of Ax+By. For example, A90+B10 is 90 mol% A and 10 mol% B.
[0044] In some embodiments, when the mixture comprises a first weight percent of the first metal-containing precursor and a second weight percent of the second metal-containing precursor, the mixture of the two precursors is introduced together (i.e., co-added). For example, the mixture of precursors may comprise about 1 wt% to about 90 wt%, or about 5 wt% to about 80 wt%, or about 20 wt% to about 60 wt% of the first metal-containing precursor and about 1 wt% to about 90 wt%, or about 5 wt% to about 80 wt%, or about 20 wt% to about 60 wt% of the second metal-containing precursor. The mixture may comprise a suitable ratio of the first metal (e.g., hafnium)-containing precursor and the second metal (e.g., aluminum)-containing precursor to form a target-type hafnium aluminum oxide material. The atomic ratio of the first metal (e.g., hafnium) containing precursor to the second metal (e.g., aluminum) containing precursor can be from about 10:1 to about 1:10, or from about 8:1 to about 1:8, or from about 5:1 to about 1:5, or from about 4:1 to about 1:4, or from about 3:1 to about 1:3, or from about 2:1 to about 1:2, or about 1:1.
[0045] The article 205 having the co-adsorbed layer 227 may then be introduced to the oxygen reactant 230 to react with the co-adsorbed layer 227 and grow a corrosion resistant coating 240 of hafnium aluminum oxide. In some embodiments, the reactant may be introduced into the ALD chamber for a second duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds.
[0046] 2A and 2B, the codeposition cycle for depositing the corrosion resistant coatings 235 and 240 can be repeated m times (where m can be an integer or a number greater than 1) to achieve a particular coating thickness. In the case of ALD, the final thickness of the material depends on the number (m) of reaction cycles performed, since each reaction cycle will grow a layer of a particular thickness, which can be an atomic layer or a fraction of an atomic layer.
[0047] As shown in FIG. 2C, in some embodiments, a sequential deposition ALD process 208 can be used to deposit a multilayer stack on an article 205. In sequential ALD, a first metal-containing precursor 210 (e.g., one or more hafnium-containing precursors or one or more aluminum-containing precursors) can be introduced into an ALD chamber and adsorb onto a surface of the article 205 to form a first adsorbed layer 229. In some embodiments, the first precursor can be pulsed into the ALD chamber for a duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. An inert gas can then be pulsed into the ALD chamber to flush out any unreacted first metal-containing precursor 210.
[0048] A reactant 230 (e.g., an oxygen-containing reactant) may then be introduced into the ALD chamber to react with the first adsorbed layer 229 to form a first metal oxide layer 239 (e.g., a hafnium oxide layer or an aluminum oxide layer). In some embodiments, the reactant may be pulsed into the ALD chamber for a duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. Any excess reactant is flushed out by introducing an inert gas into the ALD chamber. This first portion of the continuous ALD process may be repeated x times (x may be an integer or a decimal) until a first target thickness of the first metal oxide layer 239 is achieved. In some embodiments, x is greater than 1.
[0049] The first target thickness can range from about 5 Angstroms to about 100 Angstroms, from about 10 Angstroms to about 80 Angstroms, or from about 20 Angstroms to about 50 Angstroms. In some embodiments, the first target thickness can range from about 1 nm to about 1000 nm, from about 20 nm to about 500 nm, from about 20 nm to about 400 nm, from about 20 nm to about 300 nm, from about 20 nm to about 200 nm, from about 20 nm to about 100 nm, from about 50 nm to about 100 nm, or from about 20 nm to about 50 nm.
[0050] After x cycles of the first portion of the continuous ALD process, a second metal-containing precursor 220 (e.g., one or more hafnium-containing precursors or one or more aluminum-containing precursors that were not introduced in the first half-reaction) can be introduced into the ALD chamber and adsorbed onto the first metal oxide layer 239 to form a second adsorbed layer 223. In some embodiments, the second precursor can be pulsed into the ALD chamber for a duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. An inert gas can then be pulsed into the ALD chamber to flush out any unreacted second metal-containing precursor 220.
[0051] A reactant (e.g., an oxygen-containing reactant) may then be introduced into the ALD chamber to react with the second adsorbed layer 223 and form the second metal oxide layer 233. In some embodiments, the reactant may be pulsed into the ALD chamber for a duration of about 50 milliseconds to about 60 seconds, or about 1 second to about 60 seconds, or about 5 seconds to about 60 seconds, or about 10 seconds to about 60 seconds. The reactants in this second part of the continuous ALD process may be the same as or different from the reactants 230 in the first part of the continuous ALD process. Any excess reactants are flushed out by introducing an inert gas into the ALD chamber. This second part of the continuous ALD process may be repeated y times (y may be an integer or a decimal) until a second target thickness of the second metal oxide 233 is achieved. In some embodiments, y is greater than 1.
[0052] The second target thickness can range from about 5 Angstroms to about 100 Angstroms, from about 10 Angstroms to about 80 Angstroms, or from about 20 Angstroms to about 50 Angstroms. In some embodiments, the second target thickness can range from about 1 nm to about 1000 nm, from about 20 nm to about 500 nm, from about 20 nm to about 400 nm, from about 20 nm to about 300 nm, from about 20 nm to about 200 nm, from about 20 nm to about 100 nm, from about 50 nm to about 100 nm, or from about 20 nm to about 50 nm.
[0053] In some embodiments, the ratio of the thickness of each hafnium oxide layer to the thickness of each aluminum oxide layer in the alternating stack of hafnium oxide and aluminum oxide layers ranges from about 10:1 to about 1:10. For example, the thickness ratio can be from about 8:1 to about 1:8, from about 5:1 to about 1:5, from about 10:1 to about 1:1, from about 1:1 to about 1:10, from about 5:1 to about 1:1, or from about 1:1 to about 1:5. The thickness ratio can be selected according to the particular chamber application.
[0054] The first and second parts of the continuous ALD process together form a supercycle. This supercycle can be repeated m times until a target thickness of the corrosion resistant coating 245 is achieved and a target number of alternating layers of the first metal oxide and the second metal oxide is achieved. The number of supercycles, m, can be an integer or a decimal number. In some embodiments, m is greater than 1.
[0055] The relative concentrations of the first metal (e.g., hafnium) and the second metal (e.g., aluminum) in the coating can be controlled by the type of precursor used, the temperature of the ALD chamber while the precursor adsorbs on the surface of the article, the amount of time a particular precursor remains in the ALD chamber, the partial pressure of the precursor, and the like. In some embodiments, the coating can contain about 1 mol% to about 40 mol%, about 5 mol% to about 30 mol%, about 10 mol% to about 20 mol% hafnium, and about 1 mol% to about 40 mol%, about 5 mol% to about 35 mol%, or about 15 mol% to about 30 mol% aluminum. In some embodiments, the balance of the coating can be oxygen, such that the total mol% of hafnium, aluminum, and oxygen totals about 100 mol%. For example, the coating can include about 2 mol% to about 98 mol% oxygen, about 35 mol% to about 90 mol% oxygen, or about 50 mol% to about 75 mol% oxygen.
[0056] In some embodiments, the corrosion resistant coating is Hf x Al y O z (The variables x, y, and z can be positive integers or decimal values. In some embodiments, the molar ratio of aluminum to hafnium (y:x) can range from about 0.5 to about 4, from about 0.6 to about 3, from about 0.7 to about 2.8, or from about 0.8 to about 2.5. In one embodiment, the molar ratio of aluminum to hafnium can be about 2.2. In another embodiment, the molar ratio of aluminum to hafnium can be about 1.0. In one embodiment, the corrosion resistant coating can include HfAl2O5, Hf2Al2O7, or a mixture thereof.
[0057] Prior to depositing the corrosion-resistant coating 235, 240, or 245 according to any of the ALD processes described herein, an optional buffer layer can be deposited on the article 205. The buffer layer can also be deposited by an ALD process exemplified by ALD processes 200, 204, or 208. The buffer layer can include, but is not limited to, aluminum oxide (e.g., Al2O3), silicon oxide (e.g., SiO2), aluminum nitride, combinations thereof, or another suitable material. In an example where the buffer layer is alumina (Al2O3), the precursor can be an aluminum-containing precursor (e.g., trimethylaluminum (TMA)) and the reactant can be an oxygen-containing reactant (e.g., H2O). It should be understood that the corrosion-resistant coatings described herein can also be deposited on a buffer layer rather than on a surface of the article. Any of the ALD processes described herein can be used to deposit a corrosion-resistant coating on a buffer layer. In embodiments, the buffer layer can have a thickness of about 10 nm to about 1.5 μm, about 10 nm to about 15 nm, or about 0.8 μm to about 1.2 μm.
[0058] The buffer layer can provide robust mechanical properties, increase dielectric strength, provide better adhesion of the corrosion resistant coating to the component, and prevent cracking of the corrosion resistant coating at temperatures up to about 350°C, up to about 300°C, up to about 250°C, or up to about 200°C, or from about 200°C to about 350°C, or from about 250°C to about 300°C. For example, the material of construction of the chamber component to be coated can have a significantly higher coefficient of thermal expansion than the coefficient of thermal expansion of the corrosion resistant coating. By first applying a buffer layer, the deleterious effects of a mismatch in the coefficient of thermal expansion between the chamber component and the corrosion resistant coating can be managed. In some implementations, the buffer layer can include a material having a coefficient of thermal expansion between the values of the coefficient of thermal expansion of the chamber component and the coefficient of thermal expansion of the corrosion resistant coating. In addition, the buffer layer can act as a barrier to prevent migration of metal contaminants (e.g., trace metals such as Mg, Cu, etc.) from the component into the corrosion resistant coating. Adding a buffer layer under the erosion-resistant coating can increase the thermal resistance of the erosion-resistant coating as a whole by relieving elevated stresses that may be concentrated in some areas at the erosion-resistant coating / chamber component interface.
[0059] In one embodiment, the buffer layer can be Al2O3, such as amorphous Al2O3. Adding an amorphous Al2O3 layer as a buffer layer under the corrosion resistant coating can increase the thermal resistance of the corrosion resistant coating as a whole by relieving elevated pressures that may concentrate in some areas of the corrosion resistant coating / chamber component interface. Furthermore, Al2O3 has good adhesion to aluminum-based components due to their common element (i.e., aluminum). Similarly, Al2O3 has good adhesion to corrosion resistant coatings that include metal oxides, also due to their common element (i.e., oxides). Such improved interfaces reduce interface defects that tend to cause cracks. Additionally, the amorphous Al2O3 layer can act as a barrier to prevent migration of metal contaminants (e.g., trace metals such as Mg, Cu, etc.) from the component into the corrosion resistant coating.
[0060] In some embodiments, the thickness of the corrosion-resistant coating described herein can range from about 0.5 nm to about 1000 nm.In embodiments, the coating can have a maximum thickness of about 750 nm, a maximum thickness of about 500 nm, a maximum thickness of about 400 nm, a maximum thickness of about 300 nm, a maximum thickness of about 250 nm, a maximum thickness of about 200 nm, a maximum thickness of about 150 nm, a maximum thickness of about 100 nm, a maximum thickness of about 50 nm, a maximum thickness of about 30 nm, a maximum thickness of about 20 nm, or another maximum thickness.In embodiments, the coating can have a minimum thickness of about 1 nm, a minimum thickness of about 5 nm, a minimum thickness of about 10 nm, a minimum thickness of about 20 nm, a minimum thickness of about 25 nm, a minimum thickness of about 35 nm, a minimum thickness of about 50 nm, a minimum thickness of about 100 nm, a minimum thickness of about 150 nm, or another minimum thickness.
[0061] The ratio of the thickness of the corrosion-resistant coating layer to the thickness of the buffer layer, if present, can be about 200:1 to about 1:200, about 100:1 to about 1:100, or about 50:1 to about 1:50. A higher ratio of the thickness of the corrosion-resistant layer to the thickness of the buffer layer (e.g., 200:1, 100:1, 50:1, 20:1, 10:1, 5:1, 2:1, etc.) can provide better corrosion and erosion resistance, and a lower ratio of the thickness of the corrosion-resistant layer to the thickness of the buffer layer (e.g., 1:2, 1:5, 1:10, 1:20, 1:50, 1:100, 1:200) can provide better thermal resistance (e.g., improved resistance to cracking and / or delamination caused by thermal cycling). The thickness ratio can be selected according to the particular chamber application.
[0062] In addition to being a conformal process, ALD is also a uniform process and can form extremely thin films. All exposed surfaces of an article will have the same or approximately the same amount of deposited material. ALD techniques can deposit thin layers of material at relatively low temperatures (e.g., from about 20° C. to about 650° C., from about 25° C. to about 350° C., from about 20° C. to about 200° C., from about 20° C. to about 150° C., from about 20° C. to about 100° C., etc.) so as not to damage or deform any of the material of the part.
[0063] In addition, ALD techniques can also deposit conformal, uniform, continuous, low-porosity, and high-density layers of material within complex geometries, features (e.g., high aspect ratio features such as holes and apertures) and three-dimensional structures on articles. Furthermore, ALD techniques typically produce coatings that are non-porous (i.e., pinhole-free), which can eliminate crack formation during deposition. Thus, all layers deposited by ALD can be uniform, continuous, conformal, dense, and non-porous (e.g., 0% porosity).
[0064] In some embodiments, the corrosion-resistant coatings described herein have conformal and complete coverage of the underlying surface to be coated (including the coated surface features) with a uniform thickness having less than about + / - 20% thickness variation, less than about + / - 10% thickness variation, less than about + / - 5% thickness variation, or less than about + / - 5% thickness variation, as measured by comparing the thickness of the corrosion-resistant coating at one location to the thickness of the corrosion-resistant coating at another location (or as measured by obtaining the thickness of the corrosion-resistant coating at multiple locations and calculating the standard deviation of the obtained thickness values).
[0065] In some embodiments, the corrosion resistant coating can have a roughness that matches the roughness of the underlying surface being coated. In some embodiments, the corrosion resistant coating can have a surface roughness that is within about + / - 20% or less, about + / - 10% or less, or about + / - 5% or less of the surface roughness of the underlying surface being coated. In some embodiments, the surface being coated can have a surface roughness of about 120 μin to about 180 μin, about 130 μin to about 170 μin, or about 140 μin to about 160 μin.
[0066] In some embodiments, the corrosion-resistant coating can be very dense and have very low porosity compared to other deposition techniques (e.g., e-beam IAD or plasma spray). For example, the corrosion-resistant coating can have a porosity of less than about 1.5%, less than about 1%, less than about 0.5%, or less than about 0% (i.e., no porosity). As used herein, the term "no porosity / no porosity" means that there are no pores, pinholes, voids, or cracks along the entire depth of the coating as measured by transmission electron microscopy (TEM). In contrast, when using conventional e-beam IAD or plasma spray techniques, doping, or slurry-based coatings, the porosity can be 1-5%, and in some cases, can be higher.
[0067] In some embodiments, the corrosion resistant coatings described herein may have a compositional purity of about 90% to about 100%, about 95% to about 100%, about 97% to about 100%, or about 99% to about 100%, or greater than about 99.95%, or about 99.98%, as measured by laser ablation ICP-MS.
[0068] In some embodiments, after performing any of the ALD processes described herein to deposit a corrosion-resistant coating, the coating can be subjected to annealing. Annealing can be performed at temperatures ranging from about 200° C. to about 2000° C., about 400° C. to about 1800° C., about 600° C. to about 1500° C., about 800° C. to about 1200° C., and any range therein. In some embodiments, annealing temperatures up to about 500° C. can be used for the corrosion-resistant coatings described herein. Annealing can contribute to interdiffusion between various metal oxides (e.g., interdiffusion between hafnium oxide and aluminum oxide moieties) to form a homogeneous interdiffused mixed (or complex) metal oxide corrosion-resistant layer (e.g., a homogeneous interdiffused hafnium aluminum oxide layer).
[0069] In some embodiments, two or more of the above-mentioned ALD deposition techniques can be combined to produce a homogeneous metal oxide corrosion resistant coating, for example, co-deposition and co-addition can be combined, co-deposition and sequential deposition can be combined, and / or co-addition and sequential deposition can be combined.
[0070] The ALD processes described herein may optionally be preceded by cleaning the article to be coated, placing / loading the article to be coated into an ALD deposition chamber, and selecting ALD conditions (e.g., precursor types and concentrations, reactant types and concentrations, ALD temperature, pressure, etc.) for forming the corrosion resistant coating. Cleaning the article and / or selecting the ALD conditions and / or depositing the coating may all be performed by the same entity or multiple entities.
[0071] In some embodiments, the article may be cleaned with an acid solution. In one embodiment, the article is immersed in a bath of the acid solution. In an embodiment, the acid solution may be a hydrofluoric acid (HF) solution, a hydrochloric acid (HCl) solution, a nitric acid (HNO3) solution, or a combination thereof. The acid solution may remove surface contaminants from the article and / or may remove oxides from the surface of the article. Cleaning the article with an acid solution may improve the quality of a coating deposited using ALD. In one embodiment, an acid solution containing approximately 0.1-5.0 vol% HF is used to clean chamber parts made of quartz. In one embodiment, an acid solution containing approximately 0.1-20 vol% HCl is used to clean articles made of Al2O3. In one embodiment, an acid solution containing approximately 5-15 vol% HNO3 is used to clean articles made of aluminum and additional metals.
[0072] In embodiments, hafnium-containing precursors that may be used in an ALD process to deposit a corrosion resistant coating of hafnium aluminum oxide may include, but are not limited to, bis(cyclopentiadienyl)dimethylhafnium, bis(methylcyclopentadienyl)dimethylhafnium, bis(methylcyclopentadienyl)methoxymethylhafnium, hafnium(IV) t-butoxide, hafnium(IV) ethoxide, tetrakis(diethylamino)hafnium (TDMAHf), tetrakis(ethylmethylamino)hafnium (TEMAHf), tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato)hafnium(IV), HfCl4, HfCp, or any combination thereof.
[0073] In embodiments, aluminum-containing precursors that may be used in an ALD process to deposit a hafnium aluminum oxide corrosion resistant coating (or aluminum oxide buffer layer) may include, but are not limited to, trimethylaluminum (TMA), diethylaluminum ethoxide, tris(ethylmethylamido)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum (TEA), triisobutylaluminum, trimethylaluminum, tris(diethylamido)aluminum, or any combination thereof.
[0074] In embodiments, oxygen-containing reactants that may be used in an ALD process to deposit a hafnium aluminum oxide corrosion resistant coating (or aluminum oxide buffer layer) include, but are not limited to, oxygen gas (O), water vapor (HO), ozone (O), oxygen radicals (O * ), alcohol reactants, or other oxygen-containing materials. EXAMPLES
[0075] The following examples are presented to aid in the understanding of the embodiments described herein, but are not intended to specifically limit the embodiments described and claimed herein. Modifications, including substitutions of all equivalents now known or hereafter developed, and formulation changes or minor changes in experimental design that would occur to those skilled in the art are considered to be within the scope of the embodiments encompassed herein. These examples can be achieved by carrying out the methods described herein.
[0076] Example 1 - Properties of ALD deposited hafnium aluminum oxide coatings Using Rutherford backscattering / X-ray fluorescence (RBS / XRF) film stoichiometry, it was determined that the atomic concentrations of Hf, Al, and O in two hafnium aluminum oxide coatings deposited by ALD were constant throughout the film depth (i.e., homogeneous throughout the film depth). Table 1 shows the atomic concentrations of hafnium, aluminum, and oxygen for the two hafnium aluminum oxide coatings.
[0077] Table 1 - RBS / XRF data TIFF0007604476000001.tif38170
[0078] Figures 3A and 3B show the microstructure of the hafnium aluminum oxide coatings of Table 1. Figure 3A is a 20 nm scale TEM image of a Hf2Al2O7 coating deposited by ALD. Figure 3B is a 20 nm scale TEM image of a HfAl2O5 coating deposited by ALD. The TEM images of Figures 3A and 3B show that the hafnium aluminum oxide coating is amorphous, dense, non-porous, uniform, continuous and conformal.
[0079] Example 2 - FeCl3 pitting (immersion) test The corrosion resistance of two hafnium aluminum oxide coatings deposited by ALD was compared to the corrosion resistance of an aluminum oxide coating deposited by ALD based on pitting tests. Four specimens were compared: 2a) an uncoated stainless steel electropolished 316L specimen, 2b) a stainless steel electropolished 316L specimen coated with a 100 nm HfAl2O5 coating deposited by ALD, 2c) a stainless steel electropolished 316L specimen coated with a 100 nm Hf2Al2O7 coating deposited by ALD, and 2d) a stainless steel electropolished 316L specimen coated with a 100 nm Al2O3 coating deposited by ALD.
[0080] The four samples were immersed in a 6% FeCl3 solution at about 50°C for about 12 hours. The samples were then removed from the solution and the surface quality was examined for evidence of pitting. Figures 4A1, 4B1, 4C1, and 4D1 show digital camera images of the surfaces of samples 2a), 2b), 2c), and 2d), respectively, after the pitting test. Figures 4A2, 4B2, 4C2, and 4D2 show optical microscope images of areas on the surfaces of samples 2a), 2b), 2c), and 2d), respectively, that exhibited larger pitting. Figures 4A3, 4B3, 4C3, and 4D3 show optical microscope images of areas on the surfaces of samples 2a), 2b), 2c), and 2d), respectively, that exhibited smaller pitting.
[0081] As evidenced in FIGS. 4A1-4D3, the hafnium aluminum oxide coatings (i.e., samples 2b) and 2c) of FIGS. 4B1, 4B2, 4B3, 4C1, 4C2, and 4C3) showed better results in pitting (immersion) tests, which may correlate with better corrosion resistance compared to aluminum oxide coatings deposited by ALD (in FIGS. 4D1, 4D2, and 4D3) or compared to uncoated stainless steel surfaces (in FIGS. 4A1, 4A2, and 4A3).
[0082] Example 3 - HCl Bubble Test The corrosion resistance of hafnium aluminum oxide coatings deposited by ALD was compared to that of aluminum oxide coatings deposited by ALD and to that of yttrium silicon oxide coatings deposited by ALD based on HCl bubble tests. Three samples were tested: 3a) an Al 6061 coupon coated with a .about.500 nm Al2O3 coating deposited by ALD, 3b) an Al 6061 coupon coated with a .about.300 nm Hf2Al2O7 coating deposited by ALD, and 3c) an Al 6061 coupon coated with a .about.500 nm Y2Si2O7 coating deposited by ALD.
[0083] The HCl bubble test was performed by exposing a portion of each coating sample (samples 3a), 3b), and 3c)) to two HCl acid solutions (5% HCl solution and 15% HCl solution) for a period of time until a reaction between the HCl and the underlying substrate (Al 6061) was visible. This test can indicate the protection of the coating of the underlying substrate under corrosive conditions (e.g., corrosive processing conditions). The appearance of bubbles indicates that the HCl has penetrated the coating and started to react with the Al 6061 substrate underneath the coating. A longer time until bubbles (i.e., HCl penetration into the coating) is visible may correlate with better corrosion resistance and / or chamber performance.
[0084] The failure times (i.e., the time until HCl penetrates the coating and begins to react with the underlying substrate, as evidenced by the appearance of bubbles) of Samples 3a), 3b), and 3c) are summarized in Table 2 below:
[0085] Table 2 - Failure life of coatings on Al 6061 substrate TIFF0007604476000002.tif47170
[0086] As evidenced in Table 2, the failure lifetime of Sample 3b (Al 6061 coupon coated with 300 nm HfAlO deposited by ALD) in any given HCl solution was longer than that of Sample 3a (Al 6061 coupon coated with 500 nm AlO deposited by ALD) and Sample 3c (Al 6061 coupon coated with 500 nm YSiO deposited by ALD) despite having a smaller thickness.
[0087] Example 4 - HCl Immersion Test The corrosion resistance of two hafnium aluminum oxide coatings deposited by ALD was compared to the corrosion resistance of an aluminum oxide coating deposited by ALD based on an HCl soak test. Four specimens were compared: 4a) an uncoated stainless steel coupon, 4b) a stainless steel coupon coated with a 100 nm HfAl2O5 coating deposited by ALD, 4c) a stainless steel coupon coated with a 100 nm Hf2Al2O7 coating deposited by ALD, and 4d) a stainless steel coupon coated with a 100 nm Al2O3 coating deposited by ALD.
[0088] These four samples were immersed in 5% HCl solution at room temperature for about 12 hours. The samples were then removed from the solution and analyzed using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) to detect the chemical elements in the samples. Table 3 below shows a summary of the ICP-OES analysis of samples 4a), 4b), 4c), and 4d).
[0089] Table 3- ICP-OES of 5wt% HCl solution after 12 hours of immersion (ppm) TIFF0007604476000003.tif89170
[0090] As evidenced in Table 3, hafnium aluminum oxide coatings deposited by ALD (Samples 4b and 4c) enhanced the corrosion resistance of the coated stainless steel coupons in HCl solutions compared to an aluminum oxide coating deposited by ALD (Sample 4d) or compared to an uncoated stainless steel surface (Sample 4a).
[0091] Example 5 - Scratch adhesion The scratch adhesion of a 300 nm Hf2Al2O7 coating deposited by ALD to aluminum was measured by assessing the force (mN) required to expose the aluminum substrate using a 10 micron diamond stylus. The force was measured in triplicate. The results are summarized in Table 4 below.
[0092] Table 4 - Scratch adhesion test results of 300 nm Hf2Al2O7 coating on Al TIFF0007604476000004.tif59170
[0093] Example 6 - Purity Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was performed on hafnium aluminum oxide coatings (Hf2Al2O7) deposited by ALD to assess whether the coatings contained any trace elements (e.g., contaminants that diffused into the coating from the substrate). ICP-MS measurements showed that the following trace elements were all undetectable (i.e., present at less than 0.05 ppm) in the Hf2Al2O7 coating: Sb, As, Ba, Be, Bi, Br, Cd, Ca, Ce, Cs, Cr, Co, Cu, Dy, Er, Eu, Gd, Ga, Ge, Au, Ho, In, I, Ir, Fe, La, Pb, Li, Lu, Mg, Mn, Hg, Mo, Nd, Ni, Nb, Os, Pd, P, Pt, K, Pr, Re, Rh, Rb, Ru, Sm, Sc, Se, Ag, Na, Sr, Ta, Te, Tb, Tl, Th, Tm, Sn, Ti, W, U, V, Yb, Y, and Zn.
[0094] The ICP-MS data indicates that the Hf2Al2O7 coating contains mostly aluminum and hafnium (as well as trace amounts of boron (23 ppm) and zirconium (160 ppm)). The ICP-MS data confirmed that the Hf2Al2O7 coating had extremely low surface contamination (i.e., approximately 99.98% purity) and successfully prevented diffusion of trace elements from the underlying substrate into the ALD deposited coating.
[0095] Example 7 - Exposure to DCS (dichlorosilane) Corrosion of bare aluminum alloy Al6061 parts exposed to halogen gases such as DCS and residual moisture caused metal contamination on wafers for ALD processing chambers. The three-dimensional conformal, dense, non-porous Hf2Al2O7 coating acted as an effective and robust corrosion inhibitor. This was demonstrated based on the metal contamination test results, summarized in Table 5 below. The metal contamination test results were obtained after exposing uncoated and coated parts (coated with Hf2Al2O7 coating) to DSC and residual moisture at about 150°C to about 180°C for 45 minutes (corresponding to about 900 wafer processing cycles).
[0096] Table 5 - Results of DSC and metal contamination tests on exposure to residual moisture for Hf2Al2O7 coatings on Al TIFF0007604476000005.tif99170
[0097] As shown in Table 5, no metallic contamination was observed when parts coated with Hf2Al2O7 coating were exposed to DCS. In contrast, metallic contamination does occur on uncoated parts exposed to DCS under the same conditions.
[0098] Example 8 - Corrosion resistance of Hf2Al2O7 coating Aluminum specimens were coated with Hf2Al2O7 coating and immersed in Cl2 in a vacuum chamber at about 380 °C for about 25 h. No Cl2 corrosion was observed on the Hf2Al2O7 coating, as evidenced by the unchanged thickness of the Hf2Al2O7 coating before (Figure 6A) and after (Figure 6B) the immersion test.
[0099] The foregoing description sets forth numerous specific details, such as examples of specific systems, components, methods, etc., to provide a good understanding of some embodiments of the present disclosure. However, it will be apparent to one of ordinary skill in the art that at least some embodiments of the present disclosure may be practiced without these specific details. In other instances, well-known components or methods have not been described in detail or have been presented in simple block diagram form to avoid unnecessarily obscuring the present disclosure. Thus, the specific details described are merely exemplary. A particular implementation may differ from these example details and still be considered to be within the scope of the present disclosure.
[0100] Throughout this specification, a reference to "one embodiment" or "an embodiment" means that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment. In addition, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". When the term "about" or "approximately" is used herein, it is intended to mean that the nominal value presented is accurate to within ±10%.
[0101] Although the method steps herein are illustrated and described in a particular order, the order of each method step may be changed such that some steps are performed in reverse order or some steps are performed at least partially concurrently with other steps. In alternative embodiments, the order of separate steps or sub-steps may be intermittent and / or alternating.
[0102] It should be understood that the above description is intended to be illustrative and not limiting. Many other embodiments will become apparent to those skilled in the art upon reading and understanding the above description. Thus, the scope of the present disclosure should be determined with reference to the appended claims, along with the full scope of equivalents to which such claims are entitled.
Claims
1. The main body, a corrosion resistant coating on a surface of the body; A coating article comprising: the corrosion resistant coating comprises hafnium aluminum oxide comprising about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and the balance oxygen, the hafnium aluminum oxide comprising about 20 mol % to about 67 mol % oxygen; The corrosion resistant coating comprises: HfAl 2 Oh 5 、 Hf 2 A 2 O 7 or A homogeneous mixture of hafnium and aluminum having an aluminum to hafnium molar ratio ranging from about 0.8 to about 2.
5. A coated article comprising:
2. 10. The coated article of claim 1, wherein the corrosion resistant coating, at a thickness of about 300 nm, exhibits at least one of: a) at least about 13 hours to failure when tested by an HCl Bubble Test conducted in a 5% HCl solution; or b) at least about 10 hours to failure when tested by an HCl Bubble Test conducted in a 15% HCl solution.
3. The coated article of claim 1 , wherein the coated article comprises a processing chamber component that is inserted into a processing chamber.
4. 10. The coated article of claim 1, wherein the corrosion resistant coating has a thickness of about 0.5 nm to about 1 μm.
5. 10. The coated article of claim 1, which is a component of a processing chamber selected from the group consisting of a chamber wall, a showerhead, a nozzle, a plasma generating unit, a radio frequency electrode, an electrode housing, a diffuser, and a gas line.
6. 10. The coated article of claim 1, wherein the coated article comprises a portion having a depth-to-width aspect ratio in the range of about 10:1 to about 200:1, the portion being coated with the corrosion resistant coating.
7. The coated article of claim 1 , wherein the body comprises a material that is at least one of aluminum, steel, silicon, copper, or magnesium.
8. The corrosion resistant coating is 6% FeCl applied at about 50° C. for about 12 hours at a thickness of about 100 nm. 3 10. The coated article of claim 1, which exhibits less pitting corrosion in an immersion test than a 100 nm thick aluminum oxide coating.
9. 10. The coated article of claim 1, wherein the corrosion resistant coating is conformal, amorphous, has about 0% porosity, and has a uniform thickness with a thickness variation of less than about + / - 5%.
10. 10. The coated article of claim 1, wherein the corrosion resistant coating, at a thickness of about 300 nm, requires a force of at least about 52 mN to expose the surface of the body using a 10 micron diamond stylus in a scratch adhesion test.
11. 10. The coated article of claim 1, wherein the corrosion resistant coating has a purity of greater than about 99.95%.
12. 1. A method comprising performing atomic layer deposition to deposit a corrosion resistant coating on a surface of an article, comprising: the corrosion resistant coating comprises about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and the balance oxygen, the hafnium aluminum oxide comprising about 20 mol % to about 67 mol % oxygen; The corrosion resistant coating comprises: HfAl 2 Oh 5 、 Hf 2 A 2 O 7 or A homogeneous mixture of hafnium and aluminum having an aluminum to hafnium molar ratio ranging from about 0.8 to about 2.
5. Including, The article is a part of a processing chamber selected from the group consisting of a chamber wall, a showerhead, a nozzle, a plasma generating unit, a radio frequency electrode, an electrode housing, a diffuser, and a gas line; method.
13. Depositing the corrosion resistant coating includes codepositing a hafnium aluminum oxide coating on the surface of the article using atomic layer deposition, the codepositing the hafnium aluminum oxide coating comprising: contacting the surface with a hafnium-containing precursor or an aluminum-containing precursor for a first duration to form a partial adsorbed layer comprising hafnium or aluminum; contacting the partially adsorbed layer with the aluminum-containing precursor or the hafnium-containing precursor for a second duration to form a coadsorbed layer comprising hafnium and aluminum; contacting the coadsorbed layer with a reactant to form the hafnium aluminum oxide coating; The method of claim 12, comprising:
14. Depositing the corrosion resistant coating includes codepositing a hafnium aluminum oxide coating on the surface of the article using atomic layer deposition, the codepositing the hafnium aluminum oxide coating comprising: performing at least one co-addition cycle, wherein performing the at least one co-addition cycle comprises: contacting the surface with a mixture of a hafnium-containing precursor and an aluminum-containing precursor for a first duration to form a co-adsorbed layer; and contacting the coadsorbed layer with an oxygen-containing reactant to form the hafnium aluminum oxide coating. The method of claim 12.
15. 1. A method comprising depositing a hafnium aluminum oxide coating on a surface of an article using atomic layer deposition, the depositing the hafnium aluminum oxide coating comprising: contacting the surface with a hafnium-containing precursor or an aluminum-containing precursor for a first duration to form a first adsorbed layer; contacting the first adsorbent layer with an oxygen-containing reactant to form a first layer comprising hafnium oxide or aluminum oxide; contacting the first layer with an aluminum-containing precursor or a hafnium-containing precursor for a second duration to form a second adsorbed layer; contacting the second adsorbent layer with the oxygen-containing reactant to form a second layer comprising aluminum oxide or hafnium oxide, wherein when the first layer comprises hafnium oxide, the second layer comprises aluminum oxide, and when the first layer comprises aluminum oxide, the second layer comprises hafnium oxide; and forming the hafnium aluminum oxide coating from the first layer and the second layer; and Including, the hafnium aluminum oxide coating comprises about 1 mol % to about 40 mol % hafnium, about 1 mol % to about 40 mol % aluminum, and the balance oxygen, the hafnium aluminum oxide comprising about 20 mol % to about 67 mol % oxygen; The hafnium aluminum oxide coating is HfAl 2 Oh 5 、 Hf 2 A 2 O 7 or A homogeneous mixture of hafnium and aluminum having an aluminum to hafnium molar ratio ranging from about 0.8 to about 2.
5. A method comprising:
16. 16. The method of claim 15, wherein the hafnium-containing precursor comprises bis(cyclopentiadienyl)dimethylhafnium, bis(methylcyclopentadienyl)dimethylhafnium, bis(methylcyclopentadienyl)methoxymethylhafnium, hafnium(IV) t-butoxide, hafnium(IV) ethoxide, tetrakis(diethylamino)hafnium, tetrakis(ethylmethylamino)hafnium, tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato)hafnium(IV), HfCl4, HfCp, or combinations thereof.
17. 16. The method of claim 15, wherein the aluminum-containing precursor comprises trimethylaluminum (TMA), diethylaluminum ethoxide, tris(ethylmethylamido)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum (TEA), triisobutylaluminum, trimethylaluminum, or tris(diethylamido)aluminum, or a combination thereof.
Citation Information
Patent Citations
Gradient thin film
JP2003526218A
Passivation method for improving uniformity and reproducibility of atomic layer deposition and chemical vapor deposition
JP2004356612A
Hafnium oxide aluminum insulating film
JP2005529492A
Material for forming alumina thin film and heat resistant member
JP2011006755A
Apparatus and method for a deposition reactor
JP2011518256A
